(untitled) (Nigerian Dental Journal, 2026)
Background: Antimicrobial resistance (AMR) is a growing global public health threat, with inappropriate antibiotic prescribing in dentistry contributing to its acceleration. Understanding the knowledge and awareness of dental students is critical to inform educational interventions. Objective: To assess the awareness, knowledge, and ability to identify antibiotics among dental students in six Nigerian universities and evaluate associated demographic and academic factors. Methods: A cross-sectional study was conducted among dental students in clinical classes (years four to six) across six Nigerian universities: University of Nigeria, University of Port Harcourt, University of Maiduguri, Bayero University, University of Jos, and Obafemi Awolowo University. Pre-tested questionnaires were distributed electronically to each clinical class to assess demographics, awareness, and knowledge of AMR. Completed forms returned numbered 247. Statistical analyses included chi-square tests, logistic regression, one-way ANOVA, and Tukey HSD post hoc tests, with significance set at p ≤ 0.05. Results: Overall, 53.5% of students demonstrated poor knowledge of AMR. Knowledge improved with academic year (Year 4 vs. Year 6; OR = 2.449, 95% CI: 1.192–5.033; p = 0.015). No significant association was observed between gender and knowledge (p > 0.05). Significant inter-university differences were observed, with higher knowledge levels at University of Nigeria, Nsukka and Obafemi Awolowo University, Ile-Ife. Misidentification of antibiotics was common, with only 12.1% correctly identifying commonly used antibiotics. Conclusion: AMR knowledge and awareness among Nigerian dental students are suboptimal and influenced by academic year and institution rather than gender. Curriculum harmonization, structured AMR modules, and enhanced clinical exposure are essential to address these gaps. Key words: Antimicrobial resistance (AMR); Dental students; Antibiotic knowledge; Awareness.